Music Therapy as an Important Element in Shaping Communication Competences in Children with Autism Spectrum Disorder - Khyzhna, Olga; Shafranska, Karina (Journal of History Culture and Art Research, 2020)
The article concerns the problem of improving the communication of high-functioning children with autism spectrum disorder using music therapy methods. While we are witnessing the progress of research work on the language capabilities of these people, knowledge about their communication is still not sufficient. It is common ground that communication at both the language and non-language level is disturbed in these children. Music therapy can have a very positive effect on people with ASD, due to its calming and relaxing but also activating effects, depending on the type of music used. Considering the often occurring auditory hypersensitivity in these people, one should carefully select the musical material and gradually accustom them to this type of therapy, starting with sound habituation and passive music therapy. It is difficult not to notice similarities that combine music therapy with other methods that support multimodal development of children such as the Good Start Method, some elements of drama using elements of rhythm, movement and sound, logorythmics. The variety of therapeutic methods allows selection of the one that is most appropriate for a given person. Music therapy classes can have a positive impact on the psychomotor development process of a child with ASD.